YOUNG WIVES' RIGHTS OF UNREGISTERED MARRIAGE TO JOINT PROPERTY BASED ON ISLAMIC AND POSITIVE LAW - Encep Ahmad Yani (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2022)
In Indonesia, marriage is governed by two sets of legal provisions: favorable norms and Islamic rules, the latter of which are founded on the Koran, Hadith, Imam Madzhab, and the opinion of mutaakhkhirin Ulama. As for what constitutes positive legislation in this context, or law no. 16 of 2019, amending law no. 9 of 1975 concerning the clarification of Law No. 1 of 1974 concerning Marriage, and then Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Rules. This indicates that marriages are legitimate regardless of whether they are performed in front of a marriage registrar or in front of people who understand Islam's marriage laws (Kiyai, ustad, etc.). The second is permissible. Due to the fact that both are legal, the ramifications of the marriage-related rules are identical. In practice, young brides marry by hand as if there is no legal protection for common property in the event of divorce or death. People who do this research are hoping to find, develop, and come up with new ideas in the field of law, particularly in the area of protecting the rights of young people married with joint assets.